Vā. Mo. Śāha janmaśatābdī grantha - Hemāṇī, Tribhuvana Vīrajībhāī, 1904-; Śāha, Vāḍīlāla Motīlāla, 1878-1931 (Vallabha Ḍī. Gālā, 1979)
Festschrift honoring Vāḍīlāla Motīlāla Śāha, 1878-1931, Jain religious leader and political activist.